Bulgaria : Toward Blue Economy Development - World Bank (World Bank, Washington, DC, 2020)
This policy note reviews the challenges and opportunities that are central to the transition of the Republic of Bulgaria’s key marine-based economic sectors to blue economic development. The term blue economy refers to the sustainable use of ocean and maritime resources for economic growth, improved livelihoods and jobs, and the lasting health of ocean and maritime ecosystems. The note takes a closer look at sector opportunities as a mix of interconnected economic activities that complement or build on each other. The objective is to inform Bulgaria’s vision and strategy for transitioning to a blue economy. The note highlights development risks and charts a way forward, factoring in future challenges and drivers to substantially advance Bulgaria’s policy and investment alignment with the European blue economy initiatives. It also identifies the challenges and opportunities in shaping blue economy development based on a holistic ecosystem approach to the management of coastal and marine resources.